RESEARCH ON POSTPARTUM URINARY RETENTUON AND SOME RELATED FACTORS IN VAGINAL DELIVERY IN DA NANG HOSPITAL FOR WOMEN AND CHIDREN (Vietnam Journal of Community Medicine, 2021)
Objective: To determine the rate of urinary retention after vaginal delivery and evaluation some factorsrelated to urinary retention after vaginal delivery at Da Nang Hospital For Women And Chidren.Methods: Cross-sectional study describing 673 women giving birth vaginally, at Da Nang HospitalFor Women And Chidren from March 2018 to the end of September 2018. The pregnant womenin the research group will be examined, interviewed, and refer to the medical records to record thevariables according to the research questionnaire.Results: Women who are primigravida with postpartum urinary retention rate 6.6%, higher than2.4% for multigravida who have postpartum urinary retention. In infants with a weight of ≥ 3500grams, the prevalence of birth urinary retention was 16.7%, higher than that of women with babies
Keywords: Postpartum urinary retention, pregnant women, vaginal delivery